Women participating in the coffee events in Brazil (Research, Society and Development, 2022)
There is no doubt about the importance of coffee cultivation to the Brazilian economy, a fact revealed by a large number of national and international events in this sector. However, it has only been in the last two decades that women have taken part in such events, mainly because of the prejudice that prevailed until the beginning of the 21st century. The present study was carried out with the aim of identifying the profile of the women participating in the events of the coffee throughout Brazil. A total of 556 questionnaires were applied during events held in the years 2016 and 2017 in ten coffee regions of Brazil. The questioned were composed by 23 questions addressing: schooling; the areas of performance and income of women in the coffee sector. Approximately 25 per cent of the women interviewed have post-graduate level training, and only 0.6 per cent are not literate. Most women operate in the area of coffee production have the monthly income between 2 to 5 minimum wages. In general, women who work in the coffee sector and participate in events linked to the national coffee industry, work mainly in the production stage and have a high degree of education, however, receive low wages.